Kewenangan Kurator Untuk Mengurus Perseroan Terbatas Pailit - Mulyatno, Ahmad Dwi (Asas Wa Tandhim: Jurnal Hukum, Pendidikan Dan Sosial Keagamaan, 2022)
The problems in this study are: 1) What is the authority of the curator to manage a limited liability company (PT) in bankruptcy?, 2) What is the curator’s responsibility for managing the bankruptcy estate of a limited liability company (PT) in the event of the curator’s negligence or error in managing a bankruptcy?. This type of research is normative. The technique of collecting legal materials uses literature study. The analytical technique used is qualitative descriptive authority. The results show that: 1) The curator in alimited liability company (PT) bankrupt is the transfer of authority to the curator which previously was the authority of the board of Directors only with regard to the management and or settlement of assets of a limited liability company (PT) bankrupt, the authority possessed by the curator in the bankruptcy of a limited liability company (PT) arises from tasks ordered by law. The use of such authority is immediately followed by their respective responsibilities for the implementation of their authority, while the exercise of authority that is not in accordance with legal provisions and causes losses to the company will result in legal consequences for the curator. 2) The curator’s responsibility for managing the assets of a limited liability company (PT) in bankruptcy consists of the curator’s responsibility in the curator’s capacity and the curator’s personal responsibility. Result in loss of bankruptcy estate. Meanwhile, all losses that arise as a result of negligence or due to the unprofessionalism of the curator are the personal responsibility of the curator and such losses cannot be charged to the bankruptcy estate.